Field evaluation of rice genotypes for resistance and new fungicides for control of blast (Pyricularia oryzae) - R.B. SHARMA; B.N. SINGH, M.K. BARNWAL*, VAIBHAV K. SINGH (Indian Phytopathology, 2012)
One hundred and ninety three rice (Oryza sativa L.) genotypes screened for disease resistance against blastÂ caused by Pyricularia oryzae Cav. at the blast hot spot of Rice Research Farm, BAU, Ranchi showed differential reactions indicating genetic variation in rice for blast resistence. Nine genotypes viz., RP 4075-345-132-27, CN 1918, CN 1383-5-11, RR 440-167, NDR 9211, OR 1924-4, SJR 5, GP DHAN and CRHR-29) were found highly resistant to leaf blast which may be utilized as donors in resistance breeding programme. Out of six new fungicide formulations for their efficacy to control rice blast in a separate field trial with susceptible variety (CO 39), three sprays of RIL 0.13 SDC (Fenoxanil + Iso prothiolane) @ 0.2% was most effective in controlling disease with leaf blast severity of 8.8% and neck blast incidence of 4.7%. This treatment also recorded maximum grain yield of 26.6 q ha-1 with an increase of 66.4% over control. This fungicide was followed by three sprays of Baan 70 WP (tricyclazole) @ 0.06% reducing leaf blast disease severity to 11.9% and neck blast incidence to 6.2% with concomitant grain yield of 24.8 q ha-1.